Staging rebellion in the musical, Hair : marginalised voices in musical theatre - Browne, Sarah Elizabeth (Routledge advances in theatre & performance, 2023)
"This volume provides a comprehensive survey of the musical Hair and will offer critical analysis which focuses on giving voice to those who are historically considered to be on the margins of musical theatre history. Sarah Browne interrogates key scenes from the musical which will seek to identify the relationship between performance and the cultural moment. Whilst it is widely acknowledged that Hair is a product of the sixties counter-culture, this study will place the analysis in its socio-historical context to specifically reveal American values towards race, gender, and adolescence. In arguing that Hair is a rebellion against the established normative values of both American society and the art form of the musical itself, this book will suggest ways in which Hair can be considered utopian: not only as a utopian 'text' but in the practices and values it embodies, and the emotions it generates in its audiences. This book will be of great interest to scholars and students of music, musical theatre, popular music, American studies, film studies, gender studies, or African American studies"--